2015
DOI: 10.1063/1.4938200
|View full text |Cite
|
Sign up to set email alerts
|

Confocal detection of Rayleigh scattering for residual stress measurement in chemically tempered glass

Abstract: A new optical method is presented for evaluation of the stress profile in chemically tempered (chemically strengthened) glass based on confocal detection of scattered laser beam. Theoretically, a lateral resolution of 0.2 μm and a depth resolution of 0.6 μm could be achieved by using a confocal microscope with high-NA immersion objective. The stress profile in the 250 μm thick surface layer of chemically tempered lithium aluminosilicate glass was measured with a high spatial resolution to illustrate the capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The validity of the measured stress profiles was tested by the criteria of stress equilibrium (difference in the areas of compressive and tensile zones) and by comparison with Na + ion concentration profiles. Our results are compared to analogous studies by Varshneya et al, Jannotti et al and Inaba et al…”
Section: Introductionsupporting
confidence: 73%
“…The validity of the measured stress profiles was tested by the criteria of stress equilibrium (difference in the areas of compressive and tensile zones) and by comparison with Na + ion concentration profiles. Our results are compared to analogous studies by Varshneya et al, Jannotti et al and Inaba et al…”
Section: Introductionsupporting
confidence: 73%
“…Figure 4 (a) shows a comparison between the optical retardation d c y ð Þ along the curved ray path in depth coordinates (simulated using Eq. (21)) and the optical retardation d s y ð Þ (simulated directly from fully known r y ð Þ using Eq. (12)).…”
Section: Numerical Experiments Simulation Conditionsmentioning
confidence: 99%
“…Applying transmission photoelasticity to measure the stress profile can only be possible if the sample is prepared as described or cut. Automatic transmission polariscope AP-07 [20] (GlasStress Ltd.) that is equipped with magnification objective can also be used [21] instead of a manually operated polarization microscope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, these two values are obtained from a depth profiling of stress via the photoelastic effect 18 ; e.g., stress evaluation devices based on both the photoelastic effect and the waveguide effect have been commercialized and used as a standard technique. Additionally, methods using both the photoelastic effect and light scattering have been recently proposed: Using these methods, Inaba et al succeeded in evaluating the stress in two-step ion-exchanged glass 5 , and Hödemann et al demonstrated stress detection with high spatial resolution using confocal microscopy 19 .…”
mentioning
confidence: 99%